2004
DOI: 10.1002/tox.20018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of bisphenol A, 17β‐estradiol, and 17α‐ethynyl estradiol and byproduct estrogenicity

Abstract: A human breast cancer cell line (MCF-7) was used to investigate the cumulative estrogenicity profiles elicited during the oxidation of three estrogenic compounds [bisphenol A (BPA), 17beta-estradiol (E2), and 17alpha-ethynyl estradiol (EE2)]. High-performance liquid chromatography (HPLC) with a method detection limit (MDL) of approximately 1 nM was used to measure the initial and final concentrations of test compounds during oxidation. Both chlorination and ozonation removed from 75% to >99% of the test compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 24 publications
3
60
0
9
Order By: Relevance
“…Chlorine dioxide is also effective for the removal of sulfamethoxazole, roxithromycin, 17α-ethinylestradiol and diclofenac (Khetan and Collins, 2007). Chlorination and ozonation when compared for the removal of bisphenol A, 17β-estradiol, and 17α-ethinylestradiol and byproduct estrogenicity from distilled water showed comparable results with ozonation resulting in 75-99 % removal (Alum et al, 2004). Residual chlorine and ozone was found to be low with > 99 % loss of the parent compound (Gharbani et al, 2010).…”
Section: Chlorinationmentioning
confidence: 91%
See 1 more Smart Citation
“…Chlorine dioxide is also effective for the removal of sulfamethoxazole, roxithromycin, 17α-ethinylestradiol and diclofenac (Khetan and Collins, 2007). Chlorination and ozonation when compared for the removal of bisphenol A, 17β-estradiol, and 17α-ethinylestradiol and byproduct estrogenicity from distilled water showed comparable results with ozonation resulting in 75-99 % removal (Alum et al, 2004). Residual chlorine and ozone was found to be low with > 99 % loss of the parent compound (Gharbani et al, 2010).…”
Section: Chlorinationmentioning
confidence: 91%
“…Chlorination has been shown to be effective for the removal of pharmaceuticals including 17α-ethinylestradiol and 17 β-estradiol (Alum et al, 2004) and sulfonamides (Qiang et al, 2006). Chlorine dioxide is also effective for the removal of sulfamethoxazole, roxithromycin, 17α-ethinylestradiol and diclofenac (Khetan and Collins, 2007).…”
Section: Chlorinationmentioning
confidence: 99%
“…Alum et al [61] monitored both concentration and estrogenic activity of BPA during 120 min ozonation, carried out under operating conditions resembling the ones applied in full-scale drinking water treatment facilities. They observed that the level of estrogenic activity first increased and then slightly reduced before reaching stability after 60 minutes.…”
Section: Ozonationmentioning
confidence: 99%
“…Although much cheaper, chlorination is less effective than ozonation (20) and complicated by toxic as well as estrogenic byproducts. Chlorine treatment required at least two hours to remove estrogenic activity from 17 -E2 solutions, while activity in EE2 solutions was still elevated after 24 h (assessed by E-Screen) (20). Moreover, estrogenic activity was actually found to increase during the chlorination process for both 17 -E 2 and E2 (20).…”
Section: Ppm)mentioning
confidence: 99%